KEDUDUKAN HAK MILIK ATAS TANAH PADA LAHAN RUANG TERBUKA HIJAU DITINJAU DARI UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG (STUDI KASUS BANTARAN KALI OEPURA, KELURAHAN OEPURA, KECAMATAN MAULAFA, KOTA KUPANG) - Sheila F L Foenay; Husni Kusuma Dinata; Rini Marselin Kaesmetan (Petitum Law Journal, 2026)
This research is an empirical study that aims to find out and analyze the position and legal consequences of property rights to land on green open space land in terms of Law Number 26 of 2007 concerning Spatial Planning on the banks of Kali Oepura, Oepura Village, Maulafa District, Kupang City. This research was conducted in Oepura Village. The types of data used are primary data and secondary data. The data collection techniques used were interviews and literature studies. The population in this study are the Head of ATR / BPN Kupang City, Maulafa Sub-District Head, Oepura Village Head, residents who live around the banks of Oepura River. The sample used in this research is a saturated sample technique with a total of 8 respondents. This research shows that the position of property rights to land on Green Open Space (RTH) land in terms of Law Number 26 of 2007 concerning Spatial Planning on the banks of Kali Oepura, Oepura Village, Maulafa District, Kupang City is the status of property rights. Despite having legal status as property rights, these lands must still be subject to the provisions of the social function of land rights (Article 6 of the UUPA) and as RTH to avoid conflicts of public and private interests that occur in the future.